Comparison of Local Geoid Models Using Fast Fourier Transform and Least Squares Collocation in the Remove-Compute-Restore Scheme: A Case Study of Pangkal Pinang - Kuncoro, Henri; Novandi Resya Riandika (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The geoid model is crucial for all nations as the primary height reference. Given that numerous countries have developed their geoid models, local geoid modelling is essential for Indonesia. According to the Indonesian Geospatial Reference System (SRGI 2013), which encompasses the national height reference system, it is indicated that not all areas of Indonesia possess a geoid model with a high degree of accuracy. The geoid modelling in Indonesia has been conducted incrementally. In local geoid modelling utilizing gravimetric techniques, specifically within the Remove Compute Restore (RCR) framework, two approaches for ascertaining residual undulation are the Fast Fourier Transform (FFT) Method and the Least Squares Collocation (LSC) Method. This study examines a comparison of the two methods, focusing on the accuracy of the geoid model and the factors that affect its precision. This study's findings demonstrate that the least squares collocation geoid model is the most precise geoid model in the Pangkal Pinang region and its vicinity, achieving an accuracy of ±0.131 m. The accuracy of the Fast Fourier Transform method is ±0.149 m for the 2D Spherical Multiband FFT approach and ±0.159 m for Haagman's 1D Spherical FFT approach.